EFEKTIFITAS TEKNIK PEMBENIHAN ALAMI DALAM MENGOPTIMALKAN TINGKAT KELANGSUNGAN HIDUP BENIH IKAN MAS KOKI (CARRASIUS AURATUS) - DINDA DINDA; AMINULLAH AMINULLAH (Universitas Mahasaraswati K. Mataram, 2024)
The aim of this research is to describe the effectiveness of hatchery techniques in optimizing the survival rate of goldfish (Carrasius auratus) fry. This research is participatory research with a quantitative descriptive approach. The results of the research show that the technique for hatching goldfish (Carrasius auratus) is carried out using seeding stages starting from preparation of containers and media, selection of broodstock, rearing of broodstock, feeding, spawning process, hatching of eggs, rearing of larvae and rearing of fry. The effectiveness of natural goldfish hatchery techniques is classified as optimal with a fertilization rate of 87%, hatching rate of 89.6% and survival rate of goldfish seeds of 76.9%.